Efek Demokrasi Dalam Pemilihan Langsung Calon Gubernur atau Bupati - Amalik, Mulyadi J. (Unisia, 2016)
The election of local political leader (governor or resident) has lead to the rise of various conflicts among grass roots society. Not only because of the different political affiliation of people extremely vary, but also. Intervention from central government and central political party which distract the democratic process, but also feudalistic argumentation quite often raises in this process. In Yogyakarta as a case in point. The controversy raises due to the unclear definition of the distinction and particularity of Yogyakarta, in which Sultan traditionally is regarded as the most powerful man deserves to be leader and Pakualam as the vice of governor. This kind of conflicting cases will be analyzed in this article.